Preparation and in vitro characterization of scaffolds of poly(L-lactic acid) containing bioactive glass ceramic nanoparticles - Hong, Z. (2008)
Porous nanocomposite scaffolds of poly(L-lactic acid) (PLLA) containing different quantities of bioactive glass ceramic (BGC) nanoparticles (SiO2:CaO:P2O5 ! 55:40:5 (mol)) were prepared by a thermally induced phase-separation method. Dioxane was used as the solvent for PLLA. Introduction of less than 20 wt.% of BGC nanoparticles did not remarkably affect the porosity of PLLA foam. However, as the BGC content increased to 30 wt.%, the porosity of the composite was observed to decrease rapidly. The compressive modulus of the scaffolds increased from 5.5 to 8.0 MPa, while the compressive strength increased from 0.28 to 0.35 MPa as the BGC content increased from 0 to 30 wt.%. The in vitro bioactivity and biodegradability of nanocomposites were investigated by incubation in simulated body fluid (SBF) and phosphate-buffered saline, respectively. Scanning electron microscopy, energy dispersive X-ray spectroscopy, Fourier transform infrared spectroscopy and X-ray diffraction were employed to monitor the surface variation of neat PLLA and PLLA/ BGC porous scaffolds during incubation. PLLA/(20 wt.%)BGC composite exhibited the best mineralization property in SBF, while the PLLA/(10 wt.%)BGC composite showed the highest water absorption ability.